The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1413-81232015218.08942015
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento de enfermeiras e estratégias de incentivo da participação familiar na amamentação

Abstract: Conhecimento de enfermeiras e estratégias de incentivo da participação familiar na amamentação Knowledge of nurses and incentive strategies for family participation in breastfeedingResumo Objetivou-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
0
5
0
15
Order By: Relevance
“…It is worth mentioning that the participation of the woman/nursing woman, together with the support network in health education activities, such as courses, lectures and groups that address the importance of exclusive breastfeeding, has beneficial effects to the success of this practice, the clarification of doubts, transmission of knowledge and understanding of the social context that translates into support for women (24) .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the participation of the woman/nursing woman, together with the support network in health education activities, such as courses, lectures and groups that address the importance of exclusive breastfeeding, has beneficial effects to the success of this practice, the clarification of doubts, transmission of knowledge and understanding of the social context that translates into support for women (24) .…”
Section: Discussionmentioning
confidence: 99%
“…17 Corroborating this issue, a study developed with nurses in a municipality of Bahia identified that the support of fathers, family and friends, in general, is one of the essential and facilitating aspects for breastfeeding promotion. 18 Therefore, the importance of developing educational technologies not only for mothers, but also for the people who make up the support network for women is confirmed.…”
Section: /14mentioning
confidence: 99%
“…A participação dos familiares e acompanhantes nos primeiros dias de puerpério tem um valor fundamental quanto à decisão materna em continuar o AM, pois são considerados elementos chave com contato direto e integral. Devem-se as experiências negativas em torno das vivências anteriores do aleitamento, bem como tabus e crenças que acabam gerando desânimo e desencorajando as mães (11) .…”
Section: Como Não Tive Experiência Não Tenho Como Responder (éSter)unclassified